Pengaruh Tingkat Risiko Pembiayaan Musyarakah Dan Pembiayaan Mudharabah Terhadap Tingkat Profitabilitas Bank Syariah - Aditya Refinaldy; Septarina Prita Dania Sofianti; Yosefa Sayekti (STIE Mandala Jember, 2018)
This study aims to determine the influence of Risk Financing Musharakah and Risk Financing Mudharabah on Profitability Levels In sharia banks in Indonesia . The population of this research is sharia banks in Indonesia 2009-2013 period amounted to 11 based on the Indonesian Banking Statistics . Sample is 8 bank for 5 years. Data obtained by purposive sampling method. Research hypotheses were tested using multiple linear regression method and test T. The results of this study indicate that the risk of financing musyarakah significant effect on levels of profitability and risk financing mudharabah no significant effect on levels of profitability . Keywords: mudaraba, musaraka, risk, syaria bank, profitability